Tis11 mediated mRNA decay promotes the reacquisition of Drosophila intestinal stem cell quiescence. - McClelland, L.; Jasper, H.; Biteau, B. (Developmental Biology, 2017)
Adult stem cell proliferation rates are precisely regulated to maintain long-term tissue homeostasis. Defects in the mechanisms controlling stem cell proliferation result in impaired regeneration and hyperproliferative diseases. Many stem cell populations increase proliferation in response to tissue damage and reacquire basal proliferation rates after tissue repair is completed. Although proliferative signals have been extensively studied, much less is known about the molecular mechanisms that restore stem cell quiescence. Here we show that Tis11, an Adenine-uridine Rich Element (ARE) binding protein that promotes mRNA degradation, is required to re-establish basal proliferation rates of adult Drosophila intestinal stem cells (ISC) after a regenerative episode. We find that Tis11 limits ISC proliferation specifically after proliferation has been stimulated in response to heat stress or infection, and show that Tis11 expression and activity are increased in ISCs during tissue repair. Based on stem cell transcriptome analysis and RNA immunoprecipitation, we propose that Tis11 activation represents an integral part of a negative feedback mechanism that limits the expression of key components of several signaling pathways that control ISC function and proliferation. Our results identify Tis11 mediated mRNA decay as an evolutionarily conserved mechanism of re-establishing basal proliferation rates of stem cells in regenerating tissues.